A simple pre-lithium metal-doped silicon-oxygen-carbon negative electrode material and preparation method thereof

Through a two-step spray drying and one-sintering process, a multi-stage cladding layer was formed and a Li2SiO3 layer was formed on the surface, which solved the problems of low efficiency, large volume expansion and poor conductivity of silicon oxide in lithium-ion batteries, and achieved a silicon-carbon negative electrode material with high first-term efficiency, stability and rate performance.

CN116093300BActive Publication Date: 2025-04-29ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211556745.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-06
Publication Date
2025-04-29
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

In commercial applications, the existing lithium-ion battery negative electrode material, silicon oxide, faces the problems of low efficiency, large volume expansion and poor conductivity for the first time, and the coating uniformity in macro-preparation is difficult to achieve.

Method used

Through two-step differentiated spray drying and one-sintering process, a multi-stage stable cladding layer on the silicon oxygen surface is formed to inhibit volume expansion, improve conductivity, and form a Li2SiO3 layer by reacting active preliminers with sub-silicon oxide, improving the first effect and structural stability.

Benefits of technology

The silicon carbon negative electrode material that achieves high first-term efficiency, stability and rate performance is suitable for power battery negative electrodes, and has a simple process and industrial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116093300B_ABST
    Figure CN116093300B_ABST
Patent Text Reader

Abstract

The present invention relates to a simple pre-lithiated silicon oxycarbide anode material and a preparation method thereof, which are prepared through two differential spray drying processes and one sintering process. The first spray drying forms a uniformly carbon-coated surface and simultaneously introduces metal active substances; the second spray drying process protects and introduces an active lithium source, and during the sintering process, the active lithium source reacts with silicon oxide to form a Li2SiO3 layer, and the Li2SiO3 layer, together with the first modified carbon layer and the second modified carbon layer formed during the sintering process, constitutes a multi-level coating layer on the surface of silicon oxide. The presence of Li2SiO3 can inhibit the generation of irreversible substances during charge and discharge processes and improve the initial efficiency; the multi-level coating structure can effectively buffer the volume expansion during the charge and discharge processes of silicon oxide and improve the stability; metal doping enhances the structural stability, improves the electrochemical activity of the material and forms a dense interface. The material of the present invention has strong water resistance, stable structure, high capacity, high Coulomb efficiency and stable cycle, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemistry, and in particular to a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material and a preparation method thereof. Background Art

[0002] The contradiction between the increasing depletion of non-renewable energy and the energy demand of social development is becoming increasingly prominent. As a representative of secondary batteries, lithium batteries have been widely used in various fields of production and life. Faced with the urgent need to increase energy storage density, the low theoretical capacity (about 372mAh / g) of traditional graphite negative electrode materials can no longer meet the needs of high energy density batteries. Si has a good theoretical capacity (>3500 mAh / g) and is considered to be the most promising new material to replace graphite negative electrodes. However, its high volume expansion limits its commercialization process. Silicon dioxide (SiO x ) is a derivative material of Si, which also has a high theoretical specific capacity because of its Li generated by the first lithium insertion process. 2 O. Li 2 SiO 4 The inert substances make its initial efficiency lower, but the generation and distribution of inert substances inside the material can better alleviate its volume change, thus having the advantage of cyclic stability. x It has better industrial application prospects.

[0003] SiO x In the process of commercialization, the problems of low initial coulombic efficiency, large expansion and poor conductivity still need to be solved. Uniform and stable surface coating is the most critical improvement strategy. For large-scale preparation, coating uniformity is the most difficult to achieve and is also one of the key indicators. The presence of oxygen in silicon oxygen forms irreversibly delithiated substances such as lithium silicate and lithium oxide inside the particles, causing irreversible loss of lithium ions inside the battery. Silicon oxide also has the problem of low ionic and electronic conductivity, which is also a key factor affecting material performance. Based on the above problems, the researchers have made many improvements, including strategies such as uniform carbon coating on the surface, the addition of materials with excellent conductivity, and pre-consumption of internal oxygen elements, as follows.

[0004] CN 112331838A discloses a high-capacity silicon oxide composite negative electrode material for lithium-ion batteries and a preparation method thereof, wherein silicon oxide is added to a protonated chitosan solution, and then spray-dried and sintered to obtain a carbon-coated silicon oxide material, and then mixed with conductive carbon and lithium salt in a certain proportion and spray-dried to obtain a high-capacity silicon oxide composite material. However, the inert lithium source component added to the material has limited effect on improving the first-effect efficiency of silicon oxide, and the conductive carbon and lithium source doped by spray drying after sintering are easy to fall off and fail in the subsequent slurry preparation process.

[0005] CN 115207312 A discloses a double-shell silicon-oxygen material and a preparation method thereof, wherein the silicon-oxygen material is added to an organic matter and a carbon nanotube precursor solution, dried and sintered to obtain a first protective layer, and then mixed with an organic matter precursor and sintered to obtain a second coating layer. The method has poor controllability, and it is difficult to control the integrity and uniformity of the coating layer after liquid phase mixing and solid phase mixing, and it is difficult to achieve a pre-lithium effect, and the initial efficiency of the material is low, which restricts industrial application. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material and a preparation method thereof. The material is mainly formed by a two-step differential spray drying and a one-time sintering process to achieve multi-level stable coating on the silicon oxygen surface, inhibit volume expansion, improve overall conductivity, and alleviate side reactions between the surface and the electrolyte. The sintering process of the silicon oxygen surface and the Li formed by the active lithium 2 SiO 3 The layer can inhibit the formation of irreversible substances during the charge and discharge process and improve the initial efficiency. Metal doping can improve structural stability, improve electrochemical activity, form a dense interface, and improve the stability of lithium silicon oxide. The silicon-carbon negative electrode obtained by this preparation method has the advantages of high initial efficiency, good stability and rate performance, is suitable for the negative electrode of power batteries, and has a simple process and industrial prospects, providing a technical reference for the technical improvement and product upgrade of negative electrode materials for lithium-ion batteries.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A simple pre-lithium metal-doped silicon oxygen carbon negative electrode material comprises silicon oxide, a first modified carbon layer is coated on the outside of the silicon oxide, a second modified carbon layer is coated on the outside of the first modified carbon layer, the first modified carbon layer contains a metal active substance and conductive carbon; the second modified carbon layer contains an active pre-lithium agent and conductive carbon, the active pre-lithium agent reacts with silicon oxide to form a layer of Li 2 SiO 3 The layer, together with the first modified carbon layer and the second modified carbon layer, constructs a multi-level coating layer on the surface of silicon oxide.

[0009] Furthermore, the silicon oxide particle size is 3-5 μm, wherein the silicon-oxygen ratio is 0.9-1.1; the mass content of silicon oxide is 70-95%, the mass content of the first modified carbon layer is 0.1-10%, the mass content of the second modified carbon layer is 0.1-10%, the mass content of the total conductive carbon is 0.5-2%, the mass content of the metal active substance is 0.1-5%, and the molar ratio of silicon oxide to the active pre-lithium agent is 20:1-6:1.

[0010] The simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of the present invention is prepared by two differential spray drying processes and one sintering process. The first spray drying forms a first coated carbon layer on the surface of silicon oxide, and the metal active substance is introduced at the same time. The second spray drying realizes a secondary uniform coating of the surface, and the active pre-lithium agent is introduced at the same time. During the sintering process, the carbon source is coated twice to form the first and second modified carbon layers, and the active pre-lithium agent reacts with silicon oxide to form a layer of Li on the surface. 2 SiO 3 layer, together with the first modified carbon layer and the second modified carbon layer, construct a multi-level coating layer on the surface of silicon oxide; water is used as the solvent for the first spray drying, and a carbon source soluble in water is selected as the coating agent, preferably a carbon source that can react with the hydroxyl group on the surface of silicon oxide to form a dense carbon layer; an anhydrous organic solvent is selected as the solvent for the second spray drying, and a carbon source soluble in the organic solvent is selected, and the anhydrous organic solvent serves the purpose of protecting the active lithium source; wherein the first modified carbon layer and the second modified carbon layer both contain a small amount of conductive carbon.

[0011] Furthermore, the preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of the present invention has the following specific preparation process:

[0012] (1) preparing an acidic aqueous solution with a pH of 3, adding carbon source A, ultrasonicating and stirring to obtain aqueous solution B;

[0013] (2) Add silicon dioxide to aqueous solution B, and simultaneously dropwise add conductive carbon aqueous solution C, and ultrasonicate and stir to obtain dispersion D;

[0014] (3) adding metal salt M to dispersion D, stirring evenly to obtain dispersion C, and spray drying to obtain silicon-oxygen-carbon precursor E;

[0015] (4) Adding a carbon source F to an anhydrous organic solvent, and simultaneously dropping a conductive carbon solution G, ultrasonically stirring and uniformly stirring to obtain a dispersion H;

[0016] (5) Adding the silicon-oxygen precursor E to the dispersion H, and adding the active pre-lithium agent solution at the same time, stirring evenly and then spray drying to obtain the silicon-oxygen precursor I;

[0017] (6) The silicon-oxygen precursor I is placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. After cooling, it is crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon-oxygen-carbon negative electrode material.

[0018] Furthermore, the acid in the acidic aqueous solution in step (1) is citric acid, acetic acid, hydrochloric acid, sulfuric acid or phytic acid; and the carbon source A is one or more of chitosan, glucose, sucrose, polyvinyl alcohol, polyvinyl pyrrolidone or sodium alginate.

[0019] Furthermore, the conductive carbon in step (2) and step (4) is one of carbon nanotubes, graphene or conductive fibers, and has a solid content of 0.1-2%, preferably 0.4-1%; wherein the solvent used in the conductive carbon solution G in step (4) is one of ethanol, methanol, ethylene glycol, ethyl acetate and dimethylformamide.

[0020] Furthermore, the metal salt M in step (3) is a chloride, nitrate, citrate or acetate of Fe, Co, Ni, Mg, Ca or Zn; the anhydrous organic solvent in step (4) is ethanol, methanol, ethylene glycol, isopropanol, ethyl acetate or dimethylformamide; and the carbon source F in step (4) is phenolic resin, acrylic resin, polyethylene glycol, polyvinyl pyrrolidone, cellulose, polystyrene, citric acid or stearic acid.

[0021] Furthermore, in step (5), the active pre-lithium agent solution is a tetrahydrofuran solution of lithium hexamethyldisilazide, lithium tri-sec-butylborohydride or lithium triethylborohydride, and the concentration of the active pre-lithium agent solution is 1M.

[0022] Furthermore, the spray drying inlet temperature in step (3) is 140-200°C, the outlet temperature is 90-110°C, the feed rate is 3-12 rad / min, the air atmosphere, and the spray pressure is 0.2 MPa; the spray drying inlet temperature in step (5) is 150-190°C, the outlet temperature is 90-110°C, the feed rate is 5-12 rad / min, and the nitrogen atmosphere.

[0023] Furthermore, the sintering conditions in step (6) are two-stage sintering: heating from room temperature to 250°C, heating rate of 5°C / min, and keeping warm for 2h; then heating to 700-1000°C, heating rate of 3°C / min, keeping warm for 2-4h, and cooling naturally, using high-purity argon with a purity of 99.999% as the protective gas.

[0024] The beneficial effects of the present invention are as follows: the material of the present invention is prepared by two differential spray drying processes and one sintering process. (1) The first spray drying forms a first coated carbon layer on the surface of silicon oxide, and at the same time introduces metal doping active sites. The acid-treated protonated carbon source can achieve a firm bond between the carbon layer and the surface of silicon oxide; (2) The second spray drying achieves secondary uniform coating. The organic solvent system ensures the stability of the active lithium source and the formed carbon layer serves to protect the lithium source. The second coated carbon layer can strengthen the effect of the first coated carbon layer, thereby further improving the stability. The second spray drying process protects and introduces the active lithium source. During the sintering process, the active lithium source reacts with silicon and oxygen to generate Li 2 SiO 3layer, and at the same time introduce an external second modified carbon layer; (3) the conductive carbon added to the two spray drying slurries can ensure the through-distribution of the conductive components during the spraying and sintering process, thereby realizing a conductive network from the outside to the inside; (4) the active lithium source reacts with silicon dioxide during the sintering process to form a layer of Li 2 SiO 3 Layer, Li 2 SiO 3 The first modified carbon layer and the second modified carbon layer formed during the sintering process together form a multi-level coating layer on the silicon oxide surface. (5) The secondary spray drying coating followed by sintering can ensure that the internal metal components, conductive carbon and Li 2 SiO 3 All of them are within the carbon layer of the outer amorphous carbon, thus avoiding the shedding of components during the subsequent slurry preparation process and forming an overall complete material structure. 2 SiO 3 The formation of can inhibit the generation of irreversible substances during the charge and discharge process and improve the first effect; the multi-level coating structure can effectively buffer the volume expansion of silicon and oxygen during the charge and discharge process and improve stability; metal doping improves structural stability, improves the electrochemical activity of the material and forms a dense interface, improves the stability of lithium silicon oxide, and reduces electrolyte side reactions. The material prepared by the present invention has strong water resistance, stable structure, high capacity, high coulombic efficiency, and stable cycle, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a scanning electron microscope image of the silicon oxygen carbon material obtained in Example 1 at a magnification of 1.50KX.

[0027] Figure 2 This is the first charge and discharge curve of the silicon oxygen carbon material obtained in Example 1.

[0028] Figure 3 This is the cycle curve of the silicon oxycarbon material obtained in Example 4. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following examples, the microscopic morphology of the prepared samples was measured using a Hitachi S-3400N scanning electron microscope. The battery performance test was performed using a battery test system model LANHE CT2001A produced by Wuhan Landian Electronics Co., Ltd.

[0031] The silicon oxygen carbon negative electrode material prepared by the present invention, the conductive agent carbon black and the binder (PAA) are mixed in a mass ratio of 8:1:1 to form a slurry, which is evenly coated on a copper foil and dried to form an electrode. The electrolyte is 1.0 mol L -1 LiPF 6 The mixed organic solution, the solvent is EC:DEC:DMC with a mass ratio of 1:1:1, and the additive is 10% FEC. The diaphragm is a microporous polypropylene diaphragm, the positive electrode is a lithium sheet, and it is processed into a CR2025 button battery. The first cycle discharge test uses 100 mA / g to discharge to 0.005V, and then recharges to 2.0V. The cycle performance test uses 200mA / g for constant current charge and discharge test, the charge and discharge voltage range is 0.005~2V, and the test is carried out under a constant temperature of 25℃.

[0032] Example 1

[0033] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0034] (1) Prepare 200 mL of acetic acid aqueous solution with a pH of 3, add 2 g of chitosan, and stir evenly under ultrasonication to obtain acidic chitosan solution B;

[0035] (2) Add 10 g of silicon dioxide into solution B, and at the same time dropwise add a CNTs dispersion (solid content 0.4%) with a CNTs content of 0.1 g, and stir evenly under ultrasonication to obtain dispersion D;

[0036] (3) Add 0.5 g of ferric chloride to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 180°C, the outlet temperature to 95°C, and the feed rate to 3 rad / min to obtain precursor E.

[0037] (4) Add 2 g of phenolic resin to 200 mL of anhydrous ethanol, and at the same time dropwise add a CNTs ethyl acetate dispersion (solid content 0.4%) with a CNTs content of 0.1 g, and stir evenly under ultrasonication to obtain a dispersion H;

[0038] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 1 g of lithium hexamethyldisilazide, stir evenly, and then spray dry. Control the inlet temperature to 150°C, the outlet temperature to 95°C, and the feed rate to 5 rad / min to obtain silicon oxide precursor I.

[0039] (6) The silicon oxide precursor I was placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature was first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature was then increased to 800°C at a heating rate of 3°C / min and kept at this temperature for 2 h. After naturally cooling, the product was crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0040] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1258.6 mAh / g and the first efficiency was 83.53%, with good cycle and rate performance.

[0041] Example 2

[0042] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0043] (1) Prepare 200 mL of citric acid aqueous solution with a pH of 3, add 1 g of glucose, and stir evenly under ultrasonication to obtain acidic glucose solution B;

[0044] (2) Add 10 g of silicon dioxide into solution B, and at the same time dropwise add a graphene dispersion having a graphene content of 0.2 g (solid content 0.1%), and stir evenly under ultrasonication to obtain a dispersion D;

[0045] (3) Add 0.1 g of cobalt nitrate to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 140°C, the outlet temperature to 90°C, and the feed rate to 5 rad / min to obtain precursor E.

[0046] (4) Add 2 g of acrylic resin to 200 mL of anhydrous methanol, and at the same time dropwise add a CNTs methanol dispersion (solid content 0.1%) with a CNTs content of 0.1 g, and stir evenly under ultrasonication to obtain a dispersion H;

[0047] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 1 g of lithium tri-sec-butyl borohydride, stir evenly, and then spray dry. Control the inlet temperature to 160°C, the outlet temperature to 95°C, and the feed rate to 6 rad / min to obtain silicon oxide precursor I;

[0048] (6) The silicon oxide precursor I was placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature was first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature was then increased to 700°C at a heating rate of 3°C / min and kept at this temperature for 3 h. After naturally cooling, the product was crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0049] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1187.5 mAh / g and the first efficiency was 82.52%, with good cycle and rate performance.

[0050] Example 3

[0051] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0052] (1) Prepare 200 mL of hydrochloric acid aqueous solution with a pH of 3, add 3 g of sucrose, and stir evenly under ultrasonication to obtain acidic sucrose solution B;

[0053] (2) Add 10 g of silicon dioxide to solution B, and at the same time dropwise add a conductive fiber dispersion (solid content 2%) containing 0.2 g of conductive fiber, and stir evenly under ultrasonication to obtain a dispersion D;

[0054] (3) Add 0.2 g of calcium citrate to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 200 °C, the outlet temperature to 110 °C, and the feed rate to 12 rad / min to obtain precursor E.

[0055] (4) Add 2 g of polyethylene glycol to 200 mL of anhydrous ethylene glycol, and at the same time dropwise add a conductive fiber ethylene glycol dispersion (solid content 2%) containing 0.2 g of conductive fiber, and stir evenly under ultrasonication to obtain a dispersion H;

[0056] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 1 g of lithium triethylborohydride, stir evenly, and then spray dry. Control the inlet temperature to 170°C, the outlet temperature to 100°C, and the feed rate to 12 rad / min to obtain silicon oxide precursor I.

[0057] (6) The silicon oxide precursor I was placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature was first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature was then increased to 900°C at a heating rate of 3°C / min and kept at this temperature for 2 h. After naturally cooling, the product was crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0058] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1212.0 mAh / g and the first efficiency was 80.21%, with good cycle and rate performance.

[0059] Example 4

[0060] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0061] (1) Prepare 200 mL of sulfuric acid aqueous solution with a pH of 3, add 2 g of polyvinyl alcohol, and stir evenly under ultrasonication to obtain acidic polyvinyl alcohol solution B;

[0062] (2) Add 10 g of silicon dioxide into solution B, and at the same time dropwise add a CNTs dispersion (solid content 1%) with a CNTs content of 0.2 g, and stir evenly under ultrasonication to obtain dispersion D;

[0063] (3) Add 0.5 g of nickel acetate to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 150 °C, the outlet temperature to 95 °C, and the feed rate to 10 rad / min to obtain precursor E.

[0064] (4) Add 1 g of polyvinyl pyrrolidone to 200 mL of anhydrous isopropanol, and at the same time dropwise add a CNTs isopropanol dispersion (solid content 1%) with a CNTs content of 0.1 g, and stir evenly under ultrasonication to obtain a dispersion H;

[0065] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 1.5 g of lithium hexamethyldisilazide, stir evenly, and then spray dry. Control the inlet temperature to 180°C, the outlet temperature to 100°C, and the feed rate to 10 rad / min to obtain silicon oxide precursor I.

[0066] (6) The silicon oxide precursor I is placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature is first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a heating rate of 3°C / min and kept at this temperature for 2 h. After the temperature is naturally cooled, the product is crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0067] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1512.0 mAh / g and the first efficiency was 80.42%, with good cycle and rate performance.

[0068] Example 5

[0069] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0070] (1) Prepare 200 mL of phytic acid aqueous solution with a pH of 3, add 2 g of polyvinyl pyrrolidone, and stir evenly under ultrasonication to obtain acidic polyvinyl pyrrolidone solution B;

[0071] (2) Add 10 g of silicon dioxide into solution B, and at the same time dropwise add a CNTs dispersion (solid content 1.5%) with a CNTs content of 0.1 g, and stir evenly under ultrasonication to obtain dispersion D;

[0072] (3) Add 0.4 g of calcium chloride to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 180°C, the outlet temperature to 95°C, and the feed rate to 4 rad / min to obtain precursor E.

[0073] (4) Add 2 g of cellulose to 200 mL of anhydrous ethyl acetate, and at the same time dropwise add a CNTs ethyl acetate dispersion (solid content 1.5%) with a CNTs content of 0.1 g, and stir evenly under ultrasonication to obtain a dispersion H;

[0074] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 1.5 g of lithium tri-sec-butyl borohydride, stir evenly, and then spray dry. Control the inlet temperature to 190°C, the outlet temperature to 105°C, and the feed rate to 12 rad / min to obtain silicon oxide precursor I;

[0075] (6) The silicon oxide precursor I was placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature was first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature was then increased to 900°C at a heating rate of 3°C / min and kept at this temperature for 1.5 h. After the temperature was naturally cooled, the product was crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0076] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1112.8 mAh / g and the first efficiency was 83.25%, with good cycle and rate performance.

[0077] Example 6

[0078] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0079] (1) Prepare 200 mL of acetic acid aqueous solution with a pH of 3, add 2 g of sodium alginate, and stir evenly under ultrasonication to obtain acidic sodium alginate solution B;

[0080] (2) Add 10 g of silicon dioxide into solution B, and at the same time dropwise add a graphene dispersion having a graphene content of 0.05 g (solid content 0.5%), and stir evenly under ultrasonication to obtain a dispersion D;

[0081] (3) Add 0.5 g of ferric chloride to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 200°C, the outlet temperature to 105°C, and the feed rate to 8 rad / min to obtain precursor E.

[0082] (4) Add 2 g of sodium alginate to 200 mL of anhydrous N-N-DIMETHYLFAMIDE, and at the same time dropwise add a graphene N-N-DIMETHYLFAMIDE dispersion (solid content 0.5%) with a CNTs content of 0.05 g, and stir evenly with ultrasound to obtain a dispersion H;

[0083] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 2 g of lithium triethylborohydride, stir evenly and then spray dry, control the inlet temperature to 160°C, the outlet temperature to 90°C, and the feed rate to 5 rad / min, to obtain silicon oxide precursor I;

[0084] (6) The silicon oxide precursor I is placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature is first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a heating rate of 3°C / min and kept at this temperature for 2 h. After the temperature is naturally cooled, the product is crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0085] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1124.0 mAh / g and the first efficiency was 83.26%, with good cycle and rate performance.

[0086] Example 7

[0087] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0088] (1) Prepare 200 mL of citric acid aqueous solution with a pH of 3, add 2 g of chitosan, and stir evenly under ultrasonication to obtain acidic chitosan solution B;

[0089] (2) Add 10 g of silicon dioxide to solution B, and at the same time dropwise add a conductive fiber dispersion (solid content 1%) containing 0.3 g of conductive fiber, and stir evenly under ultrasonication to obtain a dispersion D;

[0090] (3) Add 0.2 g of nickel citrate to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 190°C, the outlet temperature to 100°C, and the feed rate to 6 rad / min to obtain precursor E.

[0091] (4) Add 2 g of citric acid to 200 mL of anhydrous ethanol, and at the same time dropwise add a conductive fiber ethyl acetate dispersion (solid content 1%) containing 0.2 g of conductive fiber, and stir evenly under ultrasonication to obtain a dispersion H;

[0092] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 2 g of lithium hexamethyldisilazide, stir evenly, and then spray dry. Control the inlet temperature to 180°C, the outlet temperature to 100°C, and the feed rate to 6 rad / min to obtain silicon oxide precursor I.

[0093] (6) The silicon oxide precursor I was placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature was first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature was then increased to 900°C at a heating rate of 3°C / min and kept at this temperature for 2 h. After naturally cooling, the product was crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0094] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1058.6 mAh / g and the first efficiency was 83.12%, with good cycle and rate performance.

[0095] Example 8

[0096] The preparation method of the simple pre-lithium metal-doped silicon oxygen carbon negative electrode material of this embodiment is as follows:

[0097] (1) Prepare 200 mL of hydrochloric acid aqueous solution with a pH of 3, add 4 g of sucrose, and stir evenly under ultrasonication to obtain acidic sucrose solution B;

[0098] (2) Add 10 g of silicon dioxide into solution B, and at the same time dropwise add a CNTs dispersion (solid content 0.8%) with a CNTs content of 0.5 g, and stir evenly under ultrasonication to obtain dispersion D;

[0099] (3) Add 0.8 g zinc acetate to dispersion D and stir to obtain dispersion C. Control the spray drying inlet temperature to 180 °C, the outlet temperature to 100 °C, and the feed rate to 5 rad / min to obtain precursor E.

[0100] (4) Add 0.5 g of stearic acid to 200 mL of anhydrous ethylene glycol, and at the same time dropwise add a CNTs ethylene glycol dispersion (solid content 0.8%) with a CNTs content of 0.5 g, and stir evenly under ultrasonication to obtain a dispersion H;

[0101] (5) Add the above silicon oxide precursor E to the dispersion H, and simultaneously add a tetrahydrofuran solution containing 1.6 g of lithium tri-sec-butyl borohydride, stir evenly, and then spray dry. Control the inlet temperature to 190°C, the outlet temperature to 100°C, and the feed rate to 8 rad / min to obtain silicon oxide precursor I;

[0102] (6) The silicon oxide precursor I is placed in a tubular furnace for high-temperature sintering under inert atmosphere protection. The temperature is first increased to 250°C at a heating rate of 5°C / min and kept at this temperature for 2 h. The temperature is then increased to 1000°C at a heating rate of 3°C / min and kept at this temperature for 1 h. After the temperature is naturally cooled, the product is crushed through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon oxide carbon negative electrode material.

[0103] The obtained silicon oxygen carbon material was prepared into a slurry, coated and assembled into a lithium ion half-cell and tested at a current density of 100 mA / g. The first charge specific capacity reached 1146.5 mAh / g and the first efficiency was 83.36%, with good cycle and rate performance.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications and improvements made within the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a simple pre-lithium metal-doped silicon-oxygen-carbon negative electrode material, characterized in that: The simple pre-lithium metal-doped silicon oxygen carbon negative electrode material is prepared by two differential spray drying processes and one sintering process. The first spray drying forms a first coated carbon layer on the surface of silicon oxide, and the metal active substance is introduced at the same time; the second spray drying realizes the secondary uniform coating of the surface, and the active pre-lithium agent is introduced at the same time; During the sintering process, the carbon source is coated twice to form the first and second modified carbon layers. At the same time, the active pre-lithium agent reacts with silicon oxide to form a Li2SiO3 layer on the surface, which together with the first modified carbon layer and the second modified carbon layer constructs a multi-level coating layer on the surface of silicon oxide. The specific preparation process is as follows: (1) preparing an acidic aqueous solution with a pH of 3, adding carbon source A, ultrasonicating and stirring to obtain aqueous solution B; (2) Add silicon dioxide to aqueous solution B, and simultaneously dropwise add conductive carbon aqueous solution C, and stir evenly with ultrasonic waves to obtain dispersion D; (3) adding metal salt M to dispersion D, stirring evenly to obtain dispersion C, and spray drying to obtain silicon-oxygen-carbon precursor E; (4) Adding a carbon source F to an anhydrous organic solvent, and simultaneously dropping a conductive carbon solution G, ultrasonically stirring and uniformly stirring to obtain a dispersion H; (5) Adding the silicon-oxygen precursor E to the dispersion H, and adding the active pre-lithium agent solution at the same time, stirring evenly and then spray drying to obtain the silicon-oxygen precursor I; (6) placing the silicon-oxygen precursor I in a tube furnace for high-temperature sintering under inert atmosphere protection, and after cooling, crushing it through a 300-mesh sieve to obtain a pre-lithium metal-doped silicon-oxygen-carbon negative electrode material; The conductive carbon in step (2) and step (4) is one of carbon nanotubes, graphene or conductive fibers; The metal salt M in step (3) is a chloride, nitrate, citrate or acetate of Fe, Co, Ni, Mg, Ca or Zn.

2. The method for preparing a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 1, characterized in that: The acid in the acidic aqueous solution in step (1) is citric acid, acetic acid, hydrochloric acid, sulfuric acid or phytic acid; the carbon source A is one or more of chitosan, glucose, sucrose, polyvinyl alcohol, polyvinyl pyrrolidone or sodium alginate.

3. The method for preparing a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 1, characterized in that: The solid content of the conductive carbon in step (2) and step (4) is 0.1-2%; wherein the solvent used in the conductive carbon solution G in step (4) is one of ethanol, methanol, ethylene glycol, ethyl acetate, and dimethylformamide.

4. The method for preparing a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 1, characterized in that: The anhydrous organic solvent in step (4) is ethanol, methanol, ethylene glycol, isopropanol, ethyl acetate or dimethylformamide; the carbon source F in step (4) is phenolic resin, acrylic resin, polyethylene glycol, polyvinyl pyrrolidone, cellulose, polystyrene, citric acid or stearic acid.

5. The method for preparing a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In step (5), the active pre-lithium agent solution is a tetrahydrofuran solution of lithium hexamethyldisilazide, lithium tri-sec-butylborohydride or lithium triethylborohydride, and the concentration of the active pre-lithium agent solution is 1M.

6. The method for preparing a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 1, characterized in that: The spray drying inlet temperature in step (3) is 140-200°C, the outlet temperature is 90-110°C, the feed rate is 3-12 rad / min, the air atmosphere, and the spray pressure is 0.2 MPa; the spray drying inlet temperature in step (5) is 150-190°C, the outlet temperature is 90-110°C, the feed rate is 5-12 rad / min, and the nitrogen atmosphere.

7. The method for preparing a simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 1, characterized in that: The sintering conditions in step (6) are two-stage sintering: heating from room temperature to 250°C at a heating rate of 5°C / min and keeping warm for 2h; then heating to 700-1000°C at a heating rate of 3°C / min and keeping warm for 2-4h, and cooling naturally, using high-purity argon gas with a purity of 99.999% as the protective gas.

8. A simple pre-lithium metal-doped silicon-oxygen-carbon negative electrode material prepared by the preparation method described in any one of claims 1 to 7, characterized in that: The negative electrode material comprises silicon dioxide, the silicon dioxide is coated with a first modified carbon layer, the first modified carbon layer is coated with a second modified carbon layer, and the first modified carbon layer contains metal active substances and conductive carbon; The second modified carbon layer contains an active pre-lithium agent and conductive carbon. The active pre-lithium agent reacts with silicon oxide to form a Li2SiO3 layer on the surface, which together with the first modified carbon layer and the second modified carbon layer constructs a multi-level coating layer on the surface of silicon oxide.

9. The simple pre-lithium metal-doped silicon oxygen carbon negative electrode material according to claim 8, characterized in that: The silicon oxide particle size is 3-5 μm, wherein the silicon-oxygen ratio is 0.9-1.1; the mass content of silicon oxide is 70-95%, the mass content of the first modified carbon layer is 0.1-10%, the mass content of the second modified carbon layer is 0.1-10%, the mass content of the total conductive carbon is 0.5-2%, the mass content of the metal active substance is 0.1-5%, and the molar ratio of silicon oxide to the active pre-lithium agent is 20:1-6:1.

Citation Information

Patent Citations

  • Silicon-oxygen negative electrode material with dual-core-shell structure as well as preparation method and application of silicon-oxygen negative electrode material

    CN115207312A

  • SIOx-based compound cathode material for lithium ion batteries and preparation method of material

    CN108493438A

  • High-capacity silicon monoxide composite negative electrode material of lithium ion battery and preparation method thereof

    CN112331838A